Social bonds, Internet usage time and bullying involvement: A study of rural secondary school students in China. - Liu, Tingting; Li, Tianliang (Child & Family Social Work, 2025)
School bullying is a prevalent problem affecting adolescents globally, which has been linked to the qualities of social bonds. In addition to the conventional environments such as families, peers and schools, the Internet is notably rising as a new living space for young students. Given that rural China has witnessed outstanding phenomena of bullying and Internet use among adolescents, the present study particularly examined how parental attachment, peer attachment, school connectedness and Internet usage time were associated with their experiences of being a bully, victim or bully victim, based on a sample of 2211 students from 25 rural secondary schools across three provinces of China. Results showed that those reporting bullying, victimization and both accounted for 30.0%, 64.6% and 26.2% of the whole sample, respectively. Multiple logistic regression analyses further revealed that maternal attachment, peer attachment and school connectedness were negatively associated with the odds of bullying involvement, whereas Internet usage time was positively associated with the odds of bullying involvement. The findings suggest the significance of building a comprehensive system for preventing school bullying in rural China, with a particular emphasis on strengthening family–school collaboration and effective guidance of Internet use.